2019
DOI: 10.1111/andr.12682
|View full text |Cite
|
Sign up to set email alerts
|

Activins, follistatin and immunoregulation in the epididymis

Abstract: Background: The interface between the epididymis and the immune system is implicated in many male reproductive pathologies. The resident immune cell populations and immune-environment within the epididymis are significantly different from the testis, which is an immune-privileged site. Moreover, the immune cell subsets and immunological responses between different regions of the epididymis vary considerably. The cauda epididymis is more susceptible to autoimmune responses than the caput in rodent models of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 84 publications
(128 reference statements)
2
20
0
1
Order By: Relevance
“…In the epididymis, macrophages are widely distributed in different segments, exhibiting unique phenotypes and function to establish and maintain an appropriate environment for sperm maturation and storage (18,38,39). Epididymal macrophages can be divided into two subsets according to their distinguished appearances.…”
Section: Discussionmentioning
confidence: 99%
“…In the epididymis, macrophages are widely distributed in different segments, exhibiting unique phenotypes and function to establish and maintain an appropriate environment for sperm maturation and storage (18,38,39). Epididymal macrophages can be divided into two subsets according to their distinguished appearances.…”
Section: Discussionmentioning
confidence: 99%
“…It needs to be noted though that other defensins such as Defb 1, 2, and 9 are expressed at much higher levels in the cauda. This indicates a complex multitude of mechanisms that contribute to the maintenance of peripheral tolerance, whilst simultaneously providing sufficient resistance to bacteria-induced damage [reviewed in ( 54 )], it is not clear to what extend their differential distribution contributes to immune tolerance and a dampened immune response towards microbes preferentially in the proximal epididymis.…”
Section: The Epididymal Response To Infection and Inflammationmentioning
confidence: 99%
“…Britan et al (66) reported that IDO is highly expressed in the mouse caput epididymis and is mainly secreted by the principal and apical cells. The drosophila mothers against the decapentaplegic protein 2/3/4 signaling pathway activated by activin A, and could regulate the expression of IDO, suggesting that activin A may be an activator of IDO expression in the mouse proximal epididymis (67). Moreover, these immune regulators may induce a tolerogenic circumstance in DCs and T cells (67,68).…”
Section: Innate Immune Molecules Indoleamine 23-dioxygenasementioning
confidence: 99%
“…The drosophila mothers against the decapentaplegic protein 2/3/4 signaling pathway activated by activin A, and could regulate the expression of IDO, suggesting that activin A may be an activator of IDO expression in the mouse proximal epididymis (67). Moreover, these immune regulators may induce a tolerogenic circumstance in DCs and T cells (67,68). Jrad-Lamine et al (69) have shown that pro-inflammatory cytokine expression is increased in the caput epididymitis of IDO-deficient mice.…”
Section: Innate Immune Molecules Indoleamine 23-dioxygenasementioning
confidence: 99%
See 1 more Smart Citation